Phygital Intelligence Proceedings of the 5th International Conference on Computational Design and Robotic Fabrication (CDRF 2023) - Yan, Chao; Chai, Hua; Sun, Tongyue; Yuan, Philip F. (Computational Design and Robotic Fabrication, 2024)
This open access book is a compilation of selected papers from 2023 DigitalFUTURES - The 5nd International Conference on Computational Design and Robotic Fabrication (CDRF 2023). The work focuses on novel techniques for computational design and robotic fabrication. The contents make valuable contributions to academic researchers, designers, and engineers in the industry. As well, readers will encounter new ideas about understanding intelligence in architecture.